2012
DOI: 10.1111/j.1600-0625.2012.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neuroserpin, a selective inhibitor of tissue‐type plasminogen activator in the human skin

Abstract: Serine protease of the fibrinolytic system and their specific inhibitors, the serine protease inhibitors (SERPINs) are implicated in a number of physiological and pathological processes in skin. The main SERPIN is the plasminogen activator inhibitor-1 (or PAI-1), which is involved in wound healing and in pathogenesis of several diseases including skin fibrosis. Another member of SERPIN superfamily, the neuroserpin (NSP), is widely expressed in the central nervous system. It has been recently detected in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Serpin E1, which besides the adipose tissue is also produced in high amounts by the endothelium, thus suggesting a link between obesity and the increased risk for thrombosis , was also found to be involved in wound healing and in the pathogenesis of skin fibrosis . Moreover, serpin E1 was detected in various cancers including melanoma, where it was considered to be a marker of poor prognosis that may impact invasion and metastatic spread due to its involvement in tissue matrix remodelling .…”
Section: Discussionmentioning
confidence: 99%
“…Serpin E1, which besides the adipose tissue is also produced in high amounts by the endothelium, thus suggesting a link between obesity and the increased risk for thrombosis , was also found to be involved in wound healing and in the pathogenesis of skin fibrosis . Moreover, serpin E1 was detected in various cancers including melanoma, where it was considered to be a marker of poor prognosis that may impact invasion and metastatic spread due to its involvement in tissue matrix remodelling .…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, the inhibitory activity of neuroserpin and the reduced generation of plasmin may be responsible for decreasing the clearance of amyloid-beta, while the decline in tPA activity may also be directly linked to the impairment in synaptic activity and cognitive function [ 35 , 36 ]. Outside the brain, it was also reported that neuroserpin is expressed in multiple types of organs including the heart, pancreas, skin, kidney and testis where it is responsible for selectively inhibiting the activity of tPA [ 37 ]. Again, in the context of cerebral ischemia, it was shown that tPA has a dual role; its beneficial effects might occur in few hours after the onset of ischemia and might have to do with its intravascular thrombolytic properties that reduce the extent of neurologic damage.…”
Section: Discussionmentioning
confidence: 99%